Róheim a paradoxy genitálních modifikací - Vrhel, František (Lidé města, 2001)
The essay discussing Róheim's Aphrodite, or the Woman with Penis (1945) - one of its objectives - tries to be the reminder of the founding personality of psychoanalytic anthropology, the reminder concentrated on Róheim's concept of ambisexuality. Perhaps the most remarkable mutation to which Róheim subjected Freuďs hypothesis was his suggestion that the animal consumed in the totem meal was only secondarily a representative of the father. At a more fundamental level, the level of the primary psychic processes, the totem represented the mother, and eating the animal an upward displacement of intercourse with the mother. This piece of interpretation introduces one of the enduring themes of Róheim's work: ambisexuality. In all forms of cultural activity he found a massive confusion of masculine and feminine elements. In accordance with this legacy the essay develops - and it i its second aim - a cross-cultural view of female sexual modifications the nucleus of which points toward the ambiguous meaning of infibulation, the meaning that is marked by a paradox, maybe even by an antinomy. Evidently, the paradox consists in the bipolarity of corresponding operations: the excision on the one hand as a move to femininity, and the infibulation on the other as its negation. It was precisely awareness of this antinomy that led some authors, in particular Georges Devereux and Michel Erlich, to explain the infibulation as a modality of phalization of vulva, comparable to the "expanded" morphological modifications known from Central and South Africa and from Micronesia. From these and similar phenomena we can infer the very reason of cultural relativity when examining the sense of these modlfications, ln other words the decomposition of ambisexuality is culturally bound, the "fullness" in Ocenia is equivalent to the "loss" in Africa. ln this way the paradox appears rather not on the level of object but on the level of explanatlon with its never-ending pretensions to be generalizing.